Coincidence of Poland's syndrome with Turner's syndrome - Anna Noczyńska; Andrzej Szuba; Elżbieta Wójcik; Beata Wikiera (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: Poland's syndrome (PS) is an inborn defect consisting in unilateral underdevelopment of the pectoralis major muscle, homolateral anomalies of upper extremity, as well as mammary gland aplasia. PS occurrence frequency is determined as 1:7000 to 1:100 000. Turner's syndrome (TS) results from lack of one sex chromosome or its incorrect structure and occurs with a frequency of 1:2000 of female sex newborns. Coincidence of both syndromes may hypothetically occur in 1:14 000 000 of females. Case report: A 5-year-old girl was diagnosed with a rare coincidence of PS and TS. It is the second description of PS and TS coincidence case in the literature. Low body mass, lymphatic edemas of the feet and developmental defect of the right hand in form of defective palm development and syndactyly were found after birth. At the age of 3, after digit separation procedure, she was referred to an endocrinologist because of short stature (83 cm, -3.35 SDS). Right pectoral muscle and right hand hypoplasia were found during physical examination as well as the presence of dysmorphic characteristics. The result of cytogenetic examination confirmed TS diagnosis. She began treatment with growth hormone at the age of 4.5 years. Conclusions: Appearance of PS in female patients with TS may dub diagnostic vigilance and delay TS diagnosis. Growth deficit in girls with PS constitutes the indication for karyotype testing.